1987
DOI: 10.1515/znc-1987-1-212
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from the Leaf Resin of Snakeweed, Gutierrezia sarothrae

Abstract: The resinous material excreted by aerial parts of snakeweed, Gutierrezia sarothrae, was analyzed for flavonoid aglycones. Six major flavonoids were characterized by their spectral data; nine minor flavonoids were identified by direct comparisons with markers. The major flavones form three pairs of isomeric products, five of which are 6,8-methoxylated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Exudate flavonoids have been reported from G. sarothrae (Pursh) Britt. (Hradetzky et al, 1987); in the same paper, the occurrence of flavonoid aglycones in extracts of G. grandis and of G. microcephala is commented. Similar substitution trends have been observed in all species studied so far, as is also evident from results on G. wrightii (Fang et al, 1986).…”
Section: Flavonoid Aglycones Of Astereae Speciesmentioning
confidence: 95%
“…Exudate flavonoids have been reported from G. sarothrae (Pursh) Britt. (Hradetzky et al, 1987); in the same paper, the occurrence of flavonoid aglycones in extracts of G. grandis and of G. microcephala is commented. Similar substitution trends have been observed in all species studied so far, as is also evident from results on G. wrightii (Fang et al, 1986).…”
Section: Flavonoid Aglycones Of Astereae Speciesmentioning
confidence: 95%
“…Natural Product Communications Vol. 11 (6) 2016 721 (28.6 mg). Fractions F3-3 (IC 50 around 2.5 µg/mL) and F3-4 (IC 50 between 2.5~5 µg/mL) were combined and further separated by HPLC on a semipreparative C 18 column (Phenomenex Luna column, 5 µm, 250 x 10 mm) eluted with a solvent gradient from CH 3 CN:H 2 O, 50:50 to 60:40 from 0 to 10 min, to 100:0 from 10 to 30 min, ending with 100% CH 3 CN from 30 to 40 min at a flow rate of 2.5 mL/min.…”
Section: Gutierrezia Diterpenesmentioning
confidence: 99%
“…The plant has been used externally to treat bee stings, snake bites, flesh wounds [3], and rheumatism [4]. Previous studies have indicated that the plant contains monoterpenes [5], volatile components such as cryptone and β -eudesmol [2], flavonoids [6], and labdane derivatives [7a,7b]. An antitumor proteinaceous substance has also been reported from the plant [8].…”
mentioning
confidence: 99%
“…There have been previous investigations of the essential oil composition of G. sarothrae from New Mexico and from Utah, USA [35][36][37]. Diterpenoids, including polyalthic acid, daniellic acid, nivenolide, and gutierrezial [31][32][33], and flavonoids, including apigenin, luteolin, calycopterin, jaceidin, sudachitin, and sarothrin [34], have been isolated and characterized from G. sarothrae extracts. The plant is an invasive weed and there have been several reports on the toxic effects of livestock grazing on G. sarothrae, causing abortions [30].…”
Section: Introductionmentioning
confidence: 99%